Implementation of lesson study among physics teachers: a preliminary study - Yoke, W. W. (Serials Publications, 2017)
Lesson Study is a form of in-service professional development for teachers where a group of teachers work together to identify long term goal(s) or problems in teaching and learning for their students, plan a lesson, conduct the lesson by one of the teachers while other group members observe the lesson, and conduct a group reflection session after the lesson. The Malaysian Ministry of Education has introduced Lesson Study as one of the methods to form professional learning communities (PLC) in schools. This paper describes the process of implementing Lesson Study among Physics teachers in a public secondary school as a form of in-service training. This study focuses on two physics teachers who participated in a series of trainings on Lesson Study and a lesson was conducted at the end of the training. Employing ethnographic study, the process of teachers undergoing the training and teaching the lesson was captured through participationobservation. Fieldnotes were taken for each session of meetings and also the research lesson conducted. Semi-structured interviews were conducted with the participants. Data collected and transcribed were analysed thematically. The preliminary findings presented in this study which includes teachers' readiness and their opinions of implementing Lesson Study. A teacher generally thinks that Lesson Study is mainly about group work. The main constraints of implementing Lesson Study at school as the teachers perceived were limited time; extra work load and group work a nature of Lesson Study. The paper also presented teachers' opinion about external parties' role in Lesson Study.